Role of Institutional Investors in the Resource Provision of the Region’s Economic Growth - KOLMYKOVA, Tatyana Sergeevna; OSTIMUK, Oleg Vladimirovich; OBUKHOVA, Anna Sergeyevna (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017, 2018)
The article examines the role of institutional investors in resource provision of the region's economic growth (on the materials of the Kursk region, Russia). The goal of the study is to analyze the current state and trends in the development of investment activities of institutional investors within the economic boundaries of a particular geographic region, the results of which allow to identify the main priority areas in the development of the investment environment for the activities of the regional economy entities under study. The scientific novelty of the study involves shaping the priority area sin the development of the region's economy based on the formation of an efficient investment environment and creation of favorable socioeconomic conditions for the activities of institutional investors. The completed study is based on the methods of economic and statistical analysis and economic modeling. The main result of the study is the development of priorities for the development of investment activities of institutional investors with the purpose of improving the resource provision of the region's economic growth.